2003
DOI: 10.1002/ajim.10223
|View full text |Cite
|
Sign up to set email alerts
|

Testicular cancer among Swedish pulp and paper workers

Abstract: This study indicates an increased risk for testicular cancer, especially seminomas, among maintenance workers, but not among process workers, in Swedish paper mills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…51-52 Interestingly, a study of occupational exposure to heat found an increased risk of testicular cancer in men exposed to both elevated temperatures (≥80°F) and reduced temperatures(≤60°F). 54 Several other occupational studies suggested that men working in maintenance at paper and pulp mills 55 and ferrosilicon plants 56 are at increased risk of testicular cancer, possibly because of high working temperatures. However, separating the effects of heat from those of other exposures in these settings is difficult.…”
Section: Heatmentioning
confidence: 99%
“…51-52 Interestingly, a study of occupational exposure to heat found an increased risk of testicular cancer in men exposed to both elevated temperatures (≥80°F) and reduced temperatures(≤60°F). 54 Several other occupational studies suggested that men working in maintenance at paper and pulp mills 55 and ferrosilicon plants 56 are at increased risk of testicular cancer, possibly because of high working temperatures. However, separating the effects of heat from those of other exposures in these settings is difficult.…”
Section: Heatmentioning
confidence: 99%
“…Although many studies have found positive associations between occupation and testicular cancer, 6,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104] no occupation has emerged as a clear risk factor for this lesion. Occupational exposures to several chemical substances have also been associated with testicular cancer.…”
Section: Occupational Exposuresmentioning
confidence: 99%
“…Pollán et al [2001] observed an elevated incidence of testicular cancer for metal workers. Andersson et al [2003] attributed an increased risk for workers in pulp and paper manufacturing to metal working. The risk for ''fitters and assemblers'' previously reported by Pearce et al [1987] is comparable to the risk estimates found in this study, where a preponderance of cases who had worked as motor vehicle mechanics was observed within this group [Pearce et al, 1987].…”
Section: Discussionmentioning
confidence: 98%
“…Although many studies found positive associations between occupation and testicular cancer [Mills et al, 1984;Garland et al, 1988;Swerdlow and Skeet, 1988;Hayes et al, 1990;Marshall et al, 1990;Tarone et al, 1991;Van den Eeden et al, 1991;Davis and Mostofi, 1993;Rhomberg et al, 1995;Knight et al, 1996;Hardell et al, 1998;Fleming et al, 1999;Andersson et al, 2003;Walschaerts et al, 2007], no particular occupation has emerged as a clear risk factor [Garner et al, 2005]. Occupational exposure to several chemical agents including phthalates and pesticides were observed to be associated with testicular cancer and their endocrine disrupting potential was discussed as a possible mode of action [Ducatman et al, 1986;Levin et al, 1987;Haughey et al, 1989;Kristensen et al, 1996;Hardell et al, 1998;Fleming et al, 1999;IARC, 1999].…”
Section: Introductionmentioning
confidence: 94%